The effect of drying process temperature and milling duration on total flavonoid levels in dry green tea (Camellia sinensis) powder - Peristiowati, Yuly; Kusnul, Zauhani; Hariyono (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigated the effect of drying process temperature and milling duration on the total flavonoid levels of dry green tea powder. It employed an experimental approach, subjecting green tea leaves to varying temperatures (40°C, 80°C, and 100°C) and milling durations (0, 1, 3, 5, and 8 hours), followed by nanoparticle production using high-energy ball milling. All data were analyzed using a two-way analysis of variance (ANOVA) test with SPSS version 28. The results demonstrated that drying temperature and milling duration significantly influenced flavonoid levels (p = 0.000), with a drying temperature of 40°C and a milling duration of 3 hours generating the optimal flavonoid concentration, beyond which flavonoid levels declined. SEM and PSA findings confirmed that particle size reduction significantly influences flavonoid availability. Therefore, controlled processing conditions could maintain green tea’s antioxidant properties. These results suggest that the food and pharmaceutical industries of green tea-based products could optimize drying and milling conditions to improve the bioavailability of flavonoids. Future research could explore additional variables, such as humidity and storage conditions, to enhance flavonoid preservation and product quality.